Miközben valahol… 1940-43 (Az ismeretlen háború 3.)
Recontextualizing the W.W.II. time home movies, is juxtaposing the extremely different lives of Europeans. The patchwork images of the "Übermensch", the "Normal" and the "Untermensch" families in Meanwhile Somewhere offers visible evidence of the private aspects of the war. Hitler's plan was simple with most of the population of occupied East and Southern Europe, destroy or enslave them. In 1942 after the Wannsee Conference the European Jews deadly destiny was decided as the Final Solution. In Meanwhile Somewhere the intimate, the brutal, the happy, the rare or clandestine amateur shots of different European amateurs home movies and clandestine shots counter point a Nazi ritual’s film, the miscegenation’s racist punishment of the two young lovers, the eighteen year old German boy, Georg-Gerhard and the seventeen year old Polish girl, Marie in occupied Poland, Scinawa Nyska village, 1940. This public punishment film document is the rondo pulse through out the piece. Mosaics of suggestive different families images stories counter point the sadist shaving: a National Socialist performance lesson to the children of the German-Polish village. Meanwhile Somewhere’s elegy accompanied by Tibor Szemzõ's visionary music. Péter Forgács